The relationship of physical activity and sleep quality: a cross-sectional study among male students / Muhammad Alif Hasme ... [et al.]. - Hasme, Muhammad Alif; Linoby, Adam; Sazali, Razif; Zulqarnain, Muhammad; Haziq, Amrun; Md Yusoff, Yusandra (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Physical inactivity and inadequate sleep represent critical public health challenges within university settings. Prior research demonstrates that a considerable number of students experience insufficient sleep and low physical activity levels, factors that can detrimentally affect both health and academic achievement [1]. This study investigates the relationship between physical activity and sleep quality among male students in the Faculty of Computer and Mathematical Sciences (FSKM) at Universiti Teknologi MARA (UiTM) Seremban 3. By systematically evaluating daily activity patterns alongside sleep metrics, our research aims to elucidate lifestyle behaviors that influence student well-being and academic performance. The findings highlight the urgent need for targeted health interventions, which may inform policy decisions and enhance campus wellness initiatives [2].